PEMANFAATAN LIMBAH CANGKANG BUAH KARET DAN GERGAJIAN KAYU MAHONI MENJADI BRIKET ARANG - Ogi Elian Aziz Arrifqi; Yuniarti Yuniarti; Noor Mirad Sari (Universitas Lambung Mangkurat, 2023)
The waste of rubber fruit shells and sawn mahogany is a biomass waste. This waste is rarely used, but it can be used as an alternative fuel, namely by making charcoal briquettes with a mixture of tapioca flour. This study aims to analyze the value of moisture content, density, ash content, volatile subtance content, bound carbon content and calorific value, and to obtain the composition of charcoal briquettes produced from a mixture of rubber fruit shells and mahogany sawn waste with good quality charcoal briquettes according to standards. . The statistical design used was a completely randomized design (CRD) with 3 replications and 5 treatments. The research procedures carried out include making charcoal, making powder, filtering, making adhesives and mixing gluing with raw materials, molding and drying charcoal briquettes. Parameters tested for charcoal briquettes include moisture content, density, ash content, volatile matter content, bound carbon content and calorific value using the American Standard Testing and Materials (ASTM D 5142 – 02) procedure. The results obtained from charcoal briquettes in this study obtained an average water content of 6.3100 - 6.9633%, density 0.3534 - 0.5800g/cm3, ash content 0.6000 - 1.1733%, volatile matter 60 .0833 – 70.0033%, bonded carbon 22.4667 - 32.7400% and for calorific value 6,171.91 – 7,397.54 cal/g. The best results were found in treatment B with a mixture of 75% rubber fruit shell waste + 25% mahogany sawn waste with a calorific value of 6,557.51 cal/g.Limbah cangkang buah karet dan gergajian kayu mahoni ini merupakan limbah biomasssa. Limbah ini jarang dimanfaatkan, namun limbah tersebut dapat dijadikan sebagai salah satu bahan bakar alternatif, yaitu dengan cara dibuat menjadi briket arang dengan campuran tepung tapioka. Penelitian ini bertujuan untuk menganalisis nilai kadar air, kerapatan, kadar abu, kandungan zat terbang, kadar karbon terikat dan nilai kalor, serta mendapatkan komposisi briket arang yang dihasilkan dari campurang cangkang buah karet dan limbah gergajian kayu mahoni dengan kualitas briket arang yang baik sesuai standar. Rancangan statistik yang dilakukan yaitu menggunakan rancangan acak lengkap (RAL) dengan 3 ulangan 5 perlakuan. Prosedur penelitian yang dilakukan diantaranya pembuatan arang, pembuatan serbuk, penyaringan, pembuatan perekat serta pencampuran perekatan dengan bahan baku, pencetakan dan pengeringan briket arang. Parameter yang diuji dari briket arang meliputi, kadar air, kerapatan, kadar abu, kandungan zat terbang, kadar karbon terikat dan nilai kalor dengan prosedur (ASTM D 5142 – 02) American Standard Testing and Material. Hasil yang diperoleh dari briket arang dalam penelitian ini memperoleh nilai rata-rata kadar air 6,3100 - 6,9633%, kerapatan 0,3534 – 0,5800g/cm3, kadar abu 0,6000 – 1,1733%, zat terbang 60,0833 – 70,0033%, karbon terikat 22,4667 - 32,7400% dan untuk nilai kalor 6.171,91 – 7.397,54 kal/g. Hasil yang terbaik yaitu terdapat pada perlakuan B yaitu dengan campuran limbah cangkang buah karet 75% + limbah gergajian kayu mahoni 25% dengan nilai kalor 6.557,51 kal/g.